Participation of Women Members in a Community – driven Development Project - S, Elakkiya; M, Asokhan (Journal of Extension Education, 2018)
A community-driven development project named ‘Pudu Vazhvu’ was launched in Tamil Nadu in November 2005 with World Bank assistance. The goal of the project was to reduce poverty among the rural poor and other vulnerable groups and to promote their empowerment, through targeted assistance for productive livelihood activities, in a more enabling village environment, adopting Community Driven Development (CDD) approach. Under this project, rural women were grouped into Self Help groups to promote their livelihood status. Hence there is a need to study the CDD-SHGs effectiveness. The study was carried out in Namakkal district in Tamil Nadu as it is one of the districts in Tamil Nadu where Pudu Vazhvu project was implemented. A sample of 132 respondents was selected from two blocks (six villages) following Proportionate Random sampling technique. The present study was undertaken to find out the participation of women project members in various activities of CDD project. The study revealed that Pudu Vazhvu project SHG women members had participated in group meetings record and account maintenance, formulating the rules and regulations and in getting loans.